Superstable criterion and superstable bounds for infinite range interaction I: two-body potentials - Rebenko, A. L.; Petrenko, S. N. (Methods of Functional Analysis and Topology, 2007)
A continuous infinite system of point particles interacting via two-body infinite-range potential is considered in the framework of classical statistical mecha ics. We propose some new criterion for interaction potentials to be superstable and give a very transparent proof of the Ruelle’s uniform bounds for a family of finite volume correlation functions. It gives a possibility to prove that for any temperature and chemical activity there exists at least one Gibbs state. This article is a generalization of the work Re98 for the case of infinite range interaction potential.